The Role of Eco-Intellectual Capital for MSME Sustainability - Badriyah, Nurul; Kamaliah, Kamaliah; Aunurrafiq, Aunurrafiq (Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
The purpose of this finding is to analyze the influence of eco-intellectual capital which is divided into green human capital, green structural capital and green relational capital on the sustainability performance of MSMEs. The study sample consisted of 155 MSMEs in Bangko District, Rokan Hilir Regency, Riau Province. The study used quantitative method which employs a questionnaire-based data collection method, with questionnaires handed out to respondents without intermediaries. The study uses linear regression to analyze data. The research results show that green human capital and green structural capital significantly influences MSMEs’ sustainability performance Theoretically, the findings provide new evidence to the empirical record on the impact of green human capital, green structural capital and green relational capital on MSMEs’ sustainability performance. Practically, the study is highly beneficial for MSME actors, emphasizing the importance of green human capital and green structural capital in enhancing their sustainability.